ANALISIS STRATEGI DAN EVALUASI KINERJA PENGENTASAN KEMISKINAN DALAM PROGRAM PEMBANGUNAN DESA PERSPEKTIF EKONOMI MIKRO ISLAM - Zakiyah Zakiyah; Atika Zahra Maulida (al-Uqud : Journal of Islamic Economics, 2017)
The purpose of this study is for knowing the strategy of economic development in the village used in poverty reduction particularly in Nagara, Hulu Sungai Selatan, reviewed in perspective of micro Islam economic.The method of this research is qualitative research with the descriptive approach. Where data used is the primary data and secondary data.The results of this research are to improve the availability of distribution and expansion of various daily needs products such as health, food and clothing. Improved the life that is not only for the income, but also includes the addition of the provision of employment, improved the quality of education, and increased the cultural values and humanity. The expansion of economic and social to every individu and the whole nation. Rural development program understanding how to implement and empowering communities in any development activities, facilities, and infrastructures with a did the creativity trainings that aimed to ealleviate poverty.